Studi Distribusi Angkutan Massal Berdasarkan Sistem Aktivitas di Pusat Kota Serang - Annisa, Annisa; Akbardin, Juang; Supratman, Odih; Rukman, Rukman (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2022)
The City of Serang is preparing for the development of infrastructure and road networks, so that every region in Serang City can be well integrated. The city of Serang is a national activity center, where the urban area functions as the main hub for export-import activities, industrial activity center, as the main transportation node. Serang City needs development supported by infrastructure and road network, so that every area in Serang City can be well integrated. This research was conducted to identify the origin and destination of passengers using air transportation to obtain a model of the distribution of passenger movements in Serang City so that it can be used to predict the distribution of passenger movements in the future. The initial step of this study is to identify the origin and destination of movement in the center of Serang City through the Origin Destination Matrix (MAT). From the MAT it was made with the Detroit method which is used to produce modeling of the distribution of movements determined according to the development of the area in general and the direction of each zone. From the results of this study it can be concluded that most of the generation and attraction movements are from the east.